Students’ Perceptions of Using English Songs in Learning Vocabulary at STBA Bina Dinamika: Penelitian - Edri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to investigate students’ perceptions of using English songs in learning vocabulary at STBA Bina Dinamika. The novelty of this research lies in its focus on examining both the benefits and challenges of song-based vocabulary learning within a specific higher education EFL context. A descriptive qualitative research design was employed involving 30 second-semester students. Data were collected through Likert-scale questionnaires and semi-structured interviews, then analyzed using data reduction, data display, and conclusion drawing techniques to identify key themes. The findings reveal that most students hold positive perceptions toward the use of English songs in vocabulary learning. Approximately 85% of participants agreed that songs make learning more enjoyable and engaging. Students reported that songs improve vocabulary retention through repetition, enhance pronunciation accuracy by exposing them to authentic language input, and support contextual understanding of word meanings. Additionally, songs were found to increase motivation and reduce anxiety in the classroom. However, some challenges were identified, including difficulty understanding fast song tempo, slang expressions, and unclear pronunciation. In conclusion, English songs are perceived as an effective and enjoyable medium for vocabulary acquisition, provided that lecturers carefully select appropriate songs and offer guided learning activities.